On an energy-dependent quantum system with solutions in terms of a class of hypergeometric para-orthogonal polynomials on the unit circle - Borrego-Morell, Jorge A.; Bracciali, Cleonice F. [UNESP]; Ranga, Alagacone Sri [UNESP] (MDPI, 2020)
We study an energy-dependent potential related to the Rosen-Morse potential. We give in closed-form the expression of a system of eigenfunctions of the Schrodinger operator in terms of a class of functions associated to a family of hypergeometric para-orthogonal polynomials on the unit circle. We also present modified relations of orthogonality and an asymptotic formula. Consequently, bound state solutions can be obtained for some values of the parameters that define the model. As a particular case, we obtain the symmetric trigonometric Rosen-Morse potential for which there exists an orthogonal basis of eigenstates in a Hilbert space. By comparing the existent solutions for the symmetric trigonometric Rosen-Morse potential, an identity involving Gegenbauer polynomials is obtained.
Keywords: Asymptotic expansions; Energy-dependent potential; Hypergeometric functions; Ordinary differential equations; Orthogonal polynomials; Schrödinger equation